2021
DOI: 10.3390/jpm11121261
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Cholecystectomy Is Associated with a Lower Risk of Recurrence after Curative Resection in Early-Stage Hepatocellular Carcinoma: A 10 Year Observational Single-Center Study

Abstract: Background: Cholecystectomy has been reported to be associated with increased risk of developing hepatocellular carcinoma (HCC). However, there is little information about the impact of cholecystectomy on the outcome of HCC. Aims: To evaluate the long-term effect of concurrent cholecystectomy on recurrence and overall survival in HCC after curative hepatectomy. Patients and Methods: We retrospectively enrolled 857 patients with BCLC stage 0 or A HCC who underwent primary resection from January 2001 to June 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In a retrospective study involving 3933 patients with HCC, 9 the multifactorial analysis showed that cholecystectomy was an independent risk factor for early recurrence after hepatectomy in patients with early stage (BCLC stage O/A) HCC; however, it did not affect OS. In another retrospective study of 857 patients with early-stage HCC (BCLC stage 0/A), 10 after 1:1 PSM, multifactorial analysis demonstrated that cholecystectomy reduced recurrence after hepatic resection for early-stage HCC, with no difference in OS between the two groups. Furthermore, cholecystectomy was found to promote hepatic distant recurrence after microwave ablation in patients with HCC and was associated with elevated GGT levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study involving 3933 patients with HCC, 9 the multifactorial analysis showed that cholecystectomy was an independent risk factor for early recurrence after hepatectomy in patients with early stage (BCLC stage O/A) HCC; however, it did not affect OS. In another retrospective study of 857 patients with early-stage HCC (BCLC stage 0/A), 10 after 1:1 PSM, multifactorial analysis demonstrated that cholecystectomy reduced recurrence after hepatic resection for early-stage HCC, with no difference in OS between the two groups. Furthermore, cholecystectomy was found to promote hepatic distant recurrence after microwave ablation in patients with HCC and was associated with elevated GGT levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, intraoperative co-cholecystectomy has been suggested to impact the recurrence and survival of patients with HCC after hepatectomy. [6][7][8][9][10][11] Despite this, sufficient evidence to elucidate the relationship between cholecystectomy and HCC is lacking. To address this gap, we collected case data from patients with HCC in our hospital to explore the relationship between cholecystectomy and the postoperative recurrence and survival of patients with HCC after hepatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study showed that younger age (≤ 50 years old) was an important clinical factor for predicting early recurrence of HCC after surgery (which is consistent with previous studies). Chen et al [ 15 ] reported that age was an independent risk factor for HCC recurrence. Zhang et al [ 16 ] reported that the recurrence rate of liver cancer in younger patients was higher after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, smoking, alcoholism, non‐alcoholic fatty liver disease, obesity, and aflatoxin exposure may also lead to HCC (Cai et al., 2023). Even though surgical operations, interventional therapy, chemoradiotherapy and liver transplantation improve the prognosis of the patients, HCC recurrence rate and mortality are still high due to the high aggressiveness and treatment resistance (Chen et al., 2021; Chen et al., 2022). Traditional Chinese medicine (TCM) has been used clinically in Asia for more than 2000 years, and as has gradually been accepted by non‐Chinese people (Wang et al., 2023).…”
Section: Introductionmentioning
confidence: 99%